2018
DOI: 10.1016/j.expneurol.2017.10.005
|View full text |Cite
|
Sign up to set email alerts
|

Hypoxia-ischemia modifies postsynaptic GluN2B-containing NMDA receptor complexes in the neonatal mouse brain

Abstract: The N-methyl-D-aspartate-type glutamate receptor (NMDAR)-associated multiprotein complexes are indispensable for synaptic plasticity and cognitive functions. While purification and proteomic analyses of these signaling complexes have been performed in adult rodent and human brain, much less is known about the protein composition of NMDAR complexes in the developing brain and their modifications by neonatal hypoxicischemic (HI) brain injury. In this study, the postsynaptic density proteins were prepared from po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
16
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(17 citation statements)
references
References 76 publications
1
16
0
Order By: Relevance
“…ExNMDAR hyperactivity plays a critical role in early synaptic dysfunction and phenotype onset in HD, making it an ideal highly-upstream target for neuroprotection (Milnerwood et al, 2010(Milnerwood et al, , 2012Dau et al, 2014). GluN2B forms a key component of the NMDAR signaling hub, interacting with over 70 cytosolic and membrane proteins to influence neuronal activity and function (Lu et al, 2018). Furthermore, the subunit is subjected to post-translational processes which may be exploited to modify its function (Lussier et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…ExNMDAR hyperactivity plays a critical role in early synaptic dysfunction and phenotype onset in HD, making it an ideal highly-upstream target for neuroprotection (Milnerwood et al, 2010(Milnerwood et al, , 2012Dau et al, 2014). GluN2B forms a key component of the NMDAR signaling hub, interacting with over 70 cytosolic and membrane proteins to influence neuronal activity and function (Lu et al, 2018). Furthermore, the subunit is subjected to post-translational processes which may be exploited to modify its function (Lussier et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, the overexpression of Fyn enhances the phosphorylation of GluN2B in neonatal HIE ( Jiang et al, 2008 ) and exaggerates the neuronal damage, suggesting the pro-death role of SFK in GluN2B-mediated neuronal death. It has also been reported that in early stage of HIE, the phosphorylation of DAPK1 and the P85 subunit of PI3K ( Lu et al, 2018 ) increases. These kinases are known to phosphorylate GluN2B and amplify its downstream pro-death signals ( Takagi et al, 2003 ; Tu et al, 2010 ).…”
Section: The Nmda Receptor Is Involved In Neonatal Hypoxic-ischemic Ementioning
confidence: 87%
“…In neonatal neurons, the GluN2B/SAP102 complex is dominant, while the GluN2A/PSD95 complex gradually increases during development ( van Zundert et al, 2004 ). In the early stage after HIE, the interaction between GluN2B and MAGUK decreases ( Shao et al, 2017 ; Lu et al, 2018 ), while PSD95 subsequently increases its binding with GluN2B ( Shao et al, 2017 ).…”
Section: The Nmda Receptor Is Involved In Neonatal Hypoxic-ischemic Ementioning
confidence: 99%
See 1 more Smart Citation
“…Nav1 (neuron navigator 1) is restricted to the nervous system and appears to be involved in neuronal migration during early stages of development [ 84 ]. It has been found to be associated with NMDA receptor complexes, a system well known to be influenced by ethanol [ 85 ]. This raises the interesting possibility that Nav1 is shaping the developing brain in a way that ultimately leads to differential ethanol-mediated behavioral responses in the adult, although the fact that it was expressed in the adult brain suggests that it may be participating in other functions.…”
Section: Discussionmentioning
confidence: 99%